Cold Promoted Activation of Factor VII - Gjønniess, H (Thrombosis and Haemostasis, 1972)
Several known activators of the plasma kallikrein system were tested for the ability to induce cold promoted activation of factor VII.All the prekallikrein activators tested (EACA, trypsin, acetone, urokinase, kaolin, Liquoid, ellagic acid) revealed generation of factor VII activator activity (CPA). Simultaneously the plasma kallikrein system was activated. A good correlation was demonstrated between the factor VII activation and the kallikrein activity.Glandular kallikrein, bradykinin, or kallidin revealed no effect on the coagulation system. Thus, the correlation between the factor VII activation and the kallikrein system seemed to be restricted to plasma kallikrein.